Activated Carbon Bio-xerogels as Electrodes for Super Capacitors Applications. (2016) - Zapata-Benabithe, Zulamita; Diossa, Giovanna; Castro, Chris.D.; Quintana, Germán
Abstract: The objectives of this work are to evaluate the use of the lignin as precursor of carbon xerogels and to determinate the effect of porosity and surface functionalities on the electrochemical capacitance of the activated carbon bio-xerogels. Lignin replaced the resorcinol at a mass fraction between 0 and 0.086 (wt%). The organic carbon xerogels are H3 PO4 -activated at H3 PO4 /carbon ratio of 1/1 at 450̊C to increase pore volume and surface area. Gravimetric capacitance values at 0.125 A/g, in a three-cell configuration, ranged from 138 to 234 F/g. Sample with a 0.086 content of lignin showed the best electrochemical behavior, which was associated with the high BET surface area (1243 m 2 /g), high volume (W0 (N2 )= 0.518 cm 3 /g) and width micropores (L0 (N2 )= 1.43 nm) and to the presence of pseudo faradic effects.